Pencegahan Kanker Serviks Secara Dini di Wilayah Pesisir dan Kepulauan di Desa Waipirit Seram Bagian Barat - Siti Rochmaedah; Trysna Ayu Sukardi; Mariyati Mardjuky (BADAN PENERBIT STIEPARI PRESS, 2025)
Cervical cancer is one of the most common causes of death in women, especially in developing countries. Despite its high prevalence, many women, particularly women of childbearing age (WUS), still lack understanding of the importance of early cervical cancer prevention. One factor contributing to this low awareness is the social stigma that considers discussing reproductive health taboo. Therefore, raising awareness through health education is crucial to addressing this issue. This community service program aims to increase the knowledge of WUS in Waipirit Village about cervical cancer and how to prevent it early. The health education provided includes lectures on cervical cancer, risk factors, and the importance of routine screenings such as Pap smears and HPV vaccination as preventative measures. Furthermore, a question-and-answer session was held to provide participants with the opportunity to ask questions and seek clarification on the information they received. The method used in this activity was interactive health education, with active participant involvement. Through this approach, it is hoped that WUS will gain a better understanding and feel more comfortable discussing their reproductive health. The analysis of the pre- and post-test activities showed a significant increase in knowledge among participants after attending the counseling. This increase in knowledge was not limited to medical aspects, but also emphasized the importance of early cervical cancer prevention through routine examinations and HPV vaccination. This increased understanding indicates that the health education provided can be an effective preventative measure and is expected to reduce the number of deaths from cervical cancer in the region. Going forward, more intensive and sustainable activities should be continued, involving a wider community to increase awareness of the importance of early cervical cancer prevention.